2020
DOI: 10.3390/en13154020
|View full text |Cite
|
Sign up to set email alerts
|

The “INNOVARE” Project: Innovative Plants for Distributed Poly-Generation by Residual Biomass

Abstract: The valorization of residual biomass plays today a decisive role in the concept of “circular economy”, according to which each waste material must be reused to its maximum extent. The collection and energy valorization at the local level of biomass from forest management practices and wildfire prevention cutting can be settled in protected areas to contribute to local decarbonization, by removing power generation from fossil fuels. Despite the evident advantages of bioenergy systems, several problems still hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
(40 reference statements)
1
30
0
Order By: Relevance
“…Three energy cogeneration studies were also identified as a circular economy strategy in the forestry sector. Costa et al [1] presented a case study in Italy on the valorization of waste biomass. The use of process residue as biomass cogeneration input promoted material circularity and added value to the residue, which is a circular economy strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Three energy cogeneration studies were also identified as a circular economy strategy in the forestry sector. Costa et al [1] presented a case study in Italy on the valorization of waste biomass. The use of process residue as biomass cogeneration input promoted material circularity and added value to the residue, which is a circular economy strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Power cogeneration is an alternative that has been employed by companies to promote the circular economy [1,2]. The use of materials for cogeneration improves energy efficiency, resource circularity and reduces environmental impact [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of conversion technologies are available for energy valorization of the olive oil sector by-products, with different possible outputs. The existing literature explores the opportunities of producing: syngas, to obtain electrical and thermal energy, by feeding a heat and power biomass plant with olive pomace [55][56][57], olive stones [59,60,62], or olive tree pruning residues [54,61]; electric energy [68] through the combustion of pruning residues; methanol from olive pomace via gasification [69], or from OMW via anaerobic digestion [58,70]; biogas by means of anaerobic digestion of olive pomace [67,74] or OMWW [71]; biofuel-as a sustainable alternative of biofuels based on specialized grown crops [21]-obtained from pruning residues combustion [64], from solid part of olive pomace gasification [73], or from waste cooking oil through homogenously catalyzed esterification [19]; combustible products from olive pomace (torrefied biomass or charcoal obtained, respectively, through torrefaction or slow pyrolysis processes) as sustainable substitutes of fossil fuels, such as coal [46,65].…”
Section: Biofuel Production From Pruning Residues And/or Olive Mill Wastes or Waste Cooking Oilmentioning
confidence: 99%